PERANCANGAN TAMAN BUDAYA DI JEMBRANA - I Kadek Rezki Setia Andika; Ida Bagus Idedhyana; Ngakan Ngurah Putu Nityasa (Jurnal Teknik Gradien, 2023)
Jembrana Regency is a district in Bali Province that is famous for having arts that are unique and different from other districts, such as the arts of jegogan, jogged tubung, kendang berbarung, bungbung gebyog, cag-cag weaving, embroidery textile painting, and so on. In Jembrana Regency there is an arts building called the Ir Arts Building. Soekarno, but this building can only stage performing arts and its facilities are relatively limited. To complement the lack of facilities, a building is needed on a larger scale and can be used to preserve and develop arts and culture in Jembrana, namely in the form of a Cultural Park in Jembrana. Judging from its function, the design of the Cultural Park in Jembrana uses the basic concepts of Conservative, Educational, and Recreational using the Neo Vernacular theme, which means returning traditional building forms combined with modern building forms.